Comparison of health-care utilization pattern and its correlates among the tribal and nontribal population of Kerala - Hisham Moosan; Antony Stanley; Aslesh Ottapura Prabhakaran; Krishnapillai Vijayakumar; A K Jayasree; Soumya Gopakumar (Indian Journal of Community Medicine, 2019)
Background: The isolation from mainstream development activities, together with poverty and inaccessibility to health facilities made the tribal communities specifically vulnerable to various health problems. Objectives: This study aimed to compare the utilization of antenatal care, immunization, and supplementary nutrition services by tribal and nontribal mothers and its correlates in the selected districts. Materials and Methods: The study was a comparative cross-sectional study. The study population comprised tribal and nontribal mothers utilizing antenatal care, immunization, and supplementary nutrition services. A multi-stage cluster sampling strategy was employed for the study. The Chi-square test was used to assess the association between antenatal care services utilization, utilization of immunization services, supplementary nutrition services utilization and sociodemographic variables, and other service characteristics. Results: Effective utilization of antenatal care services was not seen in 5.6% of tribal mothers. The incidence of low-birth weight (≤2500) was significantly more among tribal mothers (31%) when compared to nontribal mothers (15%). The proportion of tribal children receiving complete immunization without delay was 74%, and among nontribal children, it was 78%. Effective immunization coverage was significantly lower among children of tribal mothers with education below high school level. Receipt of take-home ration was reported by nearly 90% of tribal and nontribal mothers. 90% of tribal mothers felt that quality of take-home ration that they received was of good quality. Conclusions: The comparison of health-care utilization restricted to the domains of antenatal care, immunization services, and supplementary nutrition suggests that the tribal mothers and children had a relatively comparable utilization pattern in most of the indicators measured.